Amoxicillin/Clavulanic Acid for the Treatment of Odontogenic Infections: A Randomised Study Comparing Efficacy and Tolerability versus Clindamycin. (2nd August 2015) - Tancawan, Archiel Launch; Pato, Maria Noemi; Abidin, Khamiza Zainol; Asari, A. S. Mohd; Thong, Tran Xuan; Kochhar, Puja; Muganurmath, Chandra; Twynholm, Monique; Barker, Keith
Abstract : Background . Treatment of odontogenic infections includes surgical drainage and adjunctive antibiotics. This study was designed to generate efficacy and safety data to support twice daily dosing of amoxicillin/clavulanic acid compared to clindamycin in odontogenic infections. Methods . This was a phase IV, randomised, observer blind study; 472 subjects were randomised to receive amoxicillin/clavulanic acid (875 mg/125 mg BID, n = 235 ) or clindamycin (150 mg QID, n = 237 ) for 5 or 7 days based on clinical response. The primary endpoint was percentage of subjects achieving clinical success (composite measure of pain, swelling, fever, and additional antimicrobial therapy required) at the end of treatment. Results . The upper limit of two-sided 95% confidence interval for the treatment difference between the study arms (7.7%) was within protocol specified noninferiority margin of 10%, thus demonstrating noninferiority of amoxicillin/clavulanic acid to clindamycin. Secondary efficacy results showed a higher clinical success rate at Day 5 in the amoxicillin/clavulanic acid arm. Most adverse events (raised liver enzymes, diarrhoea, and headache) were similar across both arms and were of mild to moderate intensity. Conclusion . Amoxicillin/clavulanic acid was comparable to clindamycin in achieving clinical success (88.2% versus 89.7%) in acute odontogenic infections and the safety profile was consistent with the known side effects of both drugs. Trial Registration . This trial is registered with Clinicaltrials.gov identifier:NCT02141217 .